Satisfaction of Outpatient Services at Sarkies Asyiyah Hospital Kudus Regarding the Frequency of BPJS PRB - Zunia Khairunnisa; Yayuk Mundriyastutik; Findasari (Indonesian Health Issue, 2026)
Background: The BPJS Referral Program (PRB) is intended for patients with stable chronic diseases who require long-term care at FKTP. The frequency of PRB is influenced by patient satisfaction with the referral hospital's services. Objective: to analyze the effect of satisfaction with outpatient services at Sarkies Asyiyah Kudus Hospital on the frequency of BPJS PRB utilization. Method: A correlational analytical study with a quantitative approach was conducted on 30 outpatient respondents participating in BPJS at Sarkies Aisyiyah Kudus Hospital who were selected by Quota Sampling from 14 polyclinics. The research instrument was a patient satisfaction questionnaire based on five dimensions of SERVQUAL (Tangible, Reliability, Responsiveness, Assurance, Empathy). Data analysis used descriptive statistics, the Shapiro-Wilk normality test, Spearman correlation, and ordinal logistic regression. Results: All service quality dimensions are in the good–very good category. Spearman's test showed a significant positive relationship between patient satisfaction and the frequency of reverse referrals (p < 0.01) with the largest contribution being Tangible (ρ = 0.884). Ordinal logistic regression produced a Nagelkerke R-Square of 0.97, confirming that satisfaction explains 97% of the variation in reverse referrals. The Tangible dimension has a significant effect (p = 0.026), while the other dimensions are not significant. Conclusion: Outpatient satisfaction influences the frequency of BPJS PRB with the Tangible dimension as the dominant factor. Improvement of physical facilities and service comfort needs to be prioritized to support the effectiveness of the referral system.